After America - Birmingham, John, 1964- (New York, NY : Del Ray/Ballantine Books, 2010)
Traces the harrowing reconstruction of the United States after most of its population is killed by a natural disaster, an effort lead by President James Kipper and challenged by pirates, freebooters, and a rogue governor of Texas.
Keywords: Natural disasters -- Fiction; Regression (Civilization) -- Fiction; United States -- Fiction; Texas -- Fiction